Enhancing Methane Production Using Various Forms of Steel Shavings and Their Effect on Microbial Consortia During Anaerobic Digestion of Swine Wastewater - Lauzurique-Guerra, y; Poblete-Castro, I (Elsevier Ltd, 2024)
Addressing the increasing demand for renewable energy while efficiently treating large volumes of industrial wastewater is imperative for mitigating climate change. In this sense, the addition of various forms of iron to the anaerobic digestion process of industrial wastewaters has shown improvements in methane production to varying extents. A promising waste rich in iron is steel shavings (SS) from the steel industry. However, the effect of the SS form, whether as metal powder or Fe ions, and their concentration on methane production and microbial composition during the biodigestion of swine wastewater remains poorly understood. This study investigates batch biodigesters supplemented with either raw SS or SS dissolved in HCl (as iron ions) at various concentrations. Results indicate that adding 0.13 mM of Fe from raw SS and 0.01 mM of SS as Fe ions, methane production increased by 35 % (277 mL CH4 g VS−1) compared to control systems, with SS as Fe ions resulting in a higher methane production rate. The addition of raw SS promotes syntrophic bacteria, including acetogenic Candidatus Cloacamonas (39.4 %) and Clostridium sensu stricto (11.7 %), Synthrophomonas (9.7 %), and acetoclastic archaea Methanosaeta (0.26 %). Conversely, Proteobacteria Advenella (45.7 %) was the most prominent in biodigesters enriched with SS as Fe ions. This study is the first to demonstrate that the form of SS significantly affects the relative abundance of microorganisms using SS. Additionally, it shows that minimal supplementation of raw SS (7.26 mg/L) is sufficient to significantly enhance methane production, unlike the use of other waste iron materials. © 2024 Elsevier Ltd